REQUISITOS URBANÍSTICOS DOS SELOS VERDES NO BRASIL E O CASO DE PARAISÓPOLIS - Figueiredo, Ana Carolina Carvalho (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Sustainability is a global debate and environmental certifications are important evaluation tools in the construction industry. In this sense, this article has as main objectives, pointing them as an instrument of more sustainable projects; to mark the debate on sustainable development and the Stamps in Brazil, analyzing its requirements in terms of urban quality. Subsequently, considerations are made about the Paraisópolis Complex project that has the condominiums certified. For this, the tools of bibliographic research, documentary, interviews and field observation were applied. Finally, it is important to emphasize such requirements in the search for more sustainable cities and buildings, but with reservations about the need for them to be improved.